(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
Cattle farming is a significant contributor to the socio-economic development of Bangladesh. However, infectious diseases continuously challenge cattle farming, causing tremendous losses to farmers. Among the diseases, Lumpy Skin Disease (LSD) has become a major burden in recent years. This study was conducted to reveal the prevalence of LSD in cattle in Netrokona Sadar Upazila. Data were collected directly from the cattle farmers at Upazila Veterinary Hospital (UVH), by visiting farms, and retrospectively from the register book of UVH from November 2022 to October 2023. Of the total of 2511 observed cattle, the prevalence of LSD was the second highest (16.97%). We further investigated the prevalence of LSD according to age, sex, breed, season, vaccination status, nutrition, hygiene, and deworming. LSD was more prevalent in young (17.67%), females (18.25%), cross-breed (23.96%), and non-vaccinated (17.28%) cattle. A higher prevalence was also found in the summer (38.77%) than in other seasons. Furthermore, we found more prevalence in cattle provided with traditional diets (18.22%), in unhygienic management (17.33%), and non-dewormed (18.63%) cattle. The findings illustrated that sex, immunization status, season of the year, and diet were significantly (p<0.01) associated with the prevalence of LSD. The study will aid stakeholders in evaluating the current state of LSD in the area and developing effective control strategies against it. Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 137-147